Regeneration for sustainable marketplace: a literature review - Abd Ghapar, Muhammad Hazrin; Zakariya, Khalilah; Harun, Nor Zalina (2014)
Urban marketplace (also commonly known as the bazaar, traditional market, public market, etc.) has been recognized in published works as an important economic and cultural place for a city. Iconic marketplaces that are rich with heritage values become significant attractions in urban tourism. The desire to search for local food, traditional crafts and observing the locals’ way of life has attracted people to visit local markets and bazaars. Urban marketplace is more than just a venue for trading and commerce. Its dynamic, tangible and intangible qualities make it a vivid and inclusive public space for the local community and tourists alike. In Malaysia, a number of urban marketplaces possess cultural and heritage values, making them iconic urban attractions. However, they are facing challenges of redevelopment, gentrification and how to sustain their rich qualities, while thriving as successful commercial space for the local community. The aim of this paper is to give an overview of the qualities and characteristics of urban marketplace that are vital for cultural and economic regeneration. For this purpose, a literature review of books, journal articles and online resources are conducted to understand several terms and definitions pertaining to urban marketplace and urban regeneration. From this, the parameters of the qualities and characteristics of the marketplace which is important for cultural and economic regeneration in order to examine the study further are identified. Through urban regeneration, it is found that strategies can be formulated to rehabilitate and improve the physical, social and economic conditions of valued places in the city, such as the marketplace, as part of cultural and heritage preservation.